Hierarquia de dominância durante a obtenção de Alimento em cebus apella e cebus libidinosus em Cativeiro - Collaço, Bruno Jorge Rodrigues (2008)
The analysis of the index of hierarchy and structural models of the formation of groups allowed to establish the hierarchical position of members of two groups of the genus Cebus. By the analyses of the hierarchical positions and the application of tests to obtain a food resource (TORA), we know the difference between these groups and groups in the wild. The results show a high ranking for both Cebus apella, as well as Cebus libidinosus. The results have enabled us to establish that the hierarchical structure in groups of Cebus in captivity: a) can be fixed and rigid different from highly flexible hierarchical structure studied in groups of wild b) even which similar hierarchy indices, there are differences in the hierarchical structure presents between C. apella and C. libidinosus in captivity c) hierarchy directly influence the behavioral patterns of obtaining food in Cebus